Gender Disparity in Health and Food Expenditure in India among Elderly. (27th August 2014) - Maharana, Barsharani; Ladusingh, Laishram
Abstract : The present paper aims to shed light on the changing pattern of gender disparity in health and food expenditure over time among the elderly in India. National Sample Survey Organization (NSSO) data of the 55th (1999-2000) and the 64th (2007-2008) rounds on household consumer expenditure have been used for this study. Further, the paper examines whether change in the sex composition of the elderly in households contributes to a change in health and food expenditure. The findings indicate wide gender disparity in food and health care expenditure, with that of males being higher than that of their female counterparts; the gap, however, is narrowing with time. The compositional shift in sex among the elderly in households contributes significantly to the decline in household health and the increase in household food expenditure over time.